7x-11=-109

Simple and best practice solution for 7x-11=-109 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-11=-109 equation:


Simplifying
7x + -11 = -109

Reorder the terms:
-11 + 7x = -109

Solving
-11 + 7x = -109

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 7x = -109 + 11

Combine like terms: -11 + 11 = 0
0 + 7x = -109 + 11
7x = -109 + 11

Combine like terms: -109 + 11 = -98
7x = -98

Divide each side by '7'.
x = -14

Simplifying
x = -14

See similar equations:

| 59=-4s+8 | | 6+3(5x-6)=6-4(2x+1) | | 3b^0.5(2b^0.5+5b^3/2) | | -14+6x+7=2x+1+5x | | by=a+x | | yb=x+a | | -2(7x-1)+7=-14x+9 | | (4+9i)+(5-8i)= | | 3(4x-2)=-2(-6x+3) | | 10m^2=2m+3.14159 | | 8=-7x+4+2 | | 2(15d+45c)+5/6(12d+18c) | | 5*-1+4*5= | | 16=4x-5 | | -2k^2+72=0 | | y-12=0.666(x-6) | | -4x-1/2y=10 | | -7=4r | | 3c-2d=2 | | 3/4x-5-7/3x-1 | | 3b^1/2(2b^1/2+5b^3/2) | | 5(2x+8x)=0 | | 3x+5=12x-20 | | 3=2c-11 | | -d+-18=0 | | 1566-853= | | x*13+15=x*5+207 | | 3x-2/7=-45 | | 3.42-6.3x+1.11=22.8 | | -77-7x=9x+15 | | -2(3x+4)-2=12x-6(3x+2) | | 8y-20=0 |

Equations solver categories